Dynamic performance of a stayed highway bridge under traffic LOADS: Design predictions vs. dynamic results - Pinto, Federico (2017)
Fil: Pinto, Federico. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.